Differentiated Learning in the Subjects of the Qur'an and Hadith: Pembelajaran Berdiferensiasi dalam Mata Pelajaran Al-Qur'an dan Hadits - Abdul Gofar (Chalim Journal of Teaching and Learning, 2025)
In the process of learning the Qur'an Hadith, challenges are often encountered in maximizing the potential of students who have different abilities, interests, and learning styles so that learning seems boring, not to mention the gap in student abilities due to residence, some live in Islamic boarding schools and from home so that their knowledge of religion is very different so that a learning model is needed that is able to accommodate these differences. This study aims to analyze the application of differentiated learning in the subject of the Qur'an Hadith at MA Miftahul Qulub Mojokerto. This learning model is used as part of an effort to increase student interest in learning and optimize student potential, and determine its impact on two aspects of student development: academic and spiritual. The approach used is descriptive qualitative, with the research objects of the Qur'an Hadith teachers and students of grades X and XII in the even semester of the 2024/2025 academic year, with two study groups each using the independent curriculum. Data were collected through observation, in-depth interviews, and documentation, then analyzed using data reduction techniques, data presentation, and conclusion drawing. The research results show that the implementation of differentiated learning helps teachers adapt teaching strategies to the diverse needs of students. Both teachers and students demonstrate enthusiasm for learning and impact two aspects of student development: academic and spiritual. This method enables students with varying levels of ability to understand the subject matter better. This learning implementation is carried out systematically through three stages: planning, implementation, and evaluation, which aligns with the principles of the independent curriculum. However, challenges faced include teachers' limited time to prepare materials appropriate for each group of students and the difficulty of effectively monitoring individual development. Nevertheless, differentiated learning is considered effective in optimizing student potential.